PENGARUH INTELLECTUAL CAPITAL, INVESTMENT OPPORTUNITY SET, DAN CASH HOLDING TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Putri, Nafika Andria; Suzan, Leny (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
The study aims to evaluate the effects of cash holdings, investment opportunity sets, and intellectual capital on the value of firms in the real estate and property subsectors listed on the Indonesia Stock Exchange (IDX) between 2018 and 2022, both as a group and as individuals. The study's sample includes 40 companies from these subsectors, generating in a total of 200 observational data points. A quantitative research approach was applied, utilizing primary data sources. Descriptive statistical analysis and panel data regression analysis were used to analyze the data, with the EGLS Cross-section random effect approach being explicitly used. The findings indicated that intellectual capital, investment opportunity sets, and cash holdings collectively influence company value. However, intellectual capital alone does not affect company value, while investment opportunity sets and cash holdings positively and significantly impact company value.